2002
DOI: 10.1097/00003246-200209000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive end-expiratory pressure on gas exchange and expiratory flow limitation in adult respiratory distress syndrome*

Abstract: We conclude that on ZEEP, tidal FL is common in ARDS patients and is associated with greater regional PEEPi inhomogeneity than in NFL patients. With PEEP of 10 cm H2O, flow limitation with concurrent cyclic dynamic airway compression and re-expansion and the risk of "low lung volume injury" were absent in all patients. In FL patients, PEEP induced a significant increase in PaO2, mainly because of the reduction of regional PEEPi inequality, whereas in the NFL group, arterial oxygenation was improved satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 34 publications
2
72
0
8
Order By: Relevance
“…It was found that almost all COPD patients who require mechanical ventilation are flow limited over the entire range of tidal expiration and that the supine posture promotes flow limitation [21][22][23][24][25][26]. Another study has shown that most patients with acute respiratory failure of pulmonary origin presented with EFLT while the ones with acute respiratory failure of extrapulmonary origin did not [24].…”
Section: Clinical Significance Of Expiratory Flow Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that almost all COPD patients who require mechanical ventilation are flow limited over the entire range of tidal expiration and that the supine posture promotes flow limitation [21][22][23][24][25][26]. Another study has shown that most patients with acute respiratory failure of pulmonary origin presented with EFLT while the ones with acute respiratory failure of extrapulmonary origin did not [24].…”
Section: Clinical Significance Of Expiratory Flow Limitationmentioning
confidence: 99%
“…This method does not require performance of FVC manoeuvres, collaboration on the part of the patient or use of a body-box. It can be used during spontaneous breathing in any body position [45], during exercise [18,46,47], and in ICU settings [21][22][23][24][25][26]. With this technique the volume and time history of the control and test expiration are axiomatically the same.…”
Section: Nep Techniquementioning
confidence: 99%
“…The presence of airway closure (Stage I) and EFL (Stage II) in the tidal volume range may promote peripheral airway injury and accelerate the abnormalities of lung function [7][8][9]. This enhances inflammation due to smoke per se, leading to severe functional and structural abnormalities within the lung.…”
Section: Conventional Techniquesmentioning
confidence: 99%
“…Increased R max , rs in ARDS patients has been previously described [20,23] and attributed to decreased lung volume and time-constant inequalities [22,24]. In elderly subjects R max , rs have been described to be normal [25] or slightly decreased [26].…”
Section: Discussionmentioning
confidence: 99%